Preparation and Characterization of Chitosan Silicate Conjugate: It’s Role as a Super Disintegrant in Orally Fast Dissolving Films - Kotappa, Satheesha Babu Birur; Smriti, Podamala Rama (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: The aims of the present research work was to prepare and characterize the chitosan silicate conjugate, conjugate was included in orally fast dissolving films of levo cetirizine di hydrochloride as a super disintegrant and to compare disintegration efficiency with commercial super disintegrant. Materials and Methods: Conjugate was prepared by reacting chitosan with colloidal silicon dioxide. Characterized primarily by determining the charring point, viscosity and wicking property confirmed by Fourier transforms infrared spectroscopy, differential scanning calorimetry and X-ray powder diffraction analysis. The compatibility between the drug excipients was confirmed by Fourier transforms infrared spectroscopy and differential scanning calorimetry. Orally fast dissolving films were prepared by solvent casting technique by using hydroxypropyl methylcellulose E15, polyethylene glycol 400 as the plasticizer, conjugate and crospovidone as super disintegrants. The films were subjected to post-formulation parameters by determining weight variation, thickness, swelling index, folding endurance, tensile strength, percentage elongation, drug content, drug content uniformity, in vitro disintegration time, in vitro dissolution study, in vitro permeation study, surface morphology and accelerated stability studies. Results: The results of characterization of prepared conjugate revealed that conjugation took place. Compatibility study suggested that drug and excipients were compatible. The prepared films were having smooth surface, drug was uniformly distributed, had good physical and tensile strength. The film consists of 100 mg of conjugate as super disintegrant took less time for disintegration as compared with 100 mg of commercial super disintegrant. Conclusion: By considering the results of the present study may be concluded that the disintegration capacity of prepared conjugate was high compared to commercial disintegrant.
Keywords: Orally fast dissolving films; Chitosan silicate conjugate; Super disintegrant; Disintegration time; in vitro dissolution; in vitro permeation; Reversed phase-high; performance Liquid chromatography